1998
DOI: 10.1073/pnas.95.13.7257
|View full text |Cite
|
Sign up to set email alerts
|

Calculated 11 B– 13 C NMR chemical shift relationship in hypercoordinate methonium and boronium ions

Abstract: The boronium-carbonium continuum was extended to include hypercoordinated protonated methanes and their boron analogs. RESULTS AND DISCUSSIONThe structures of the hypercoordinate protonated methanes and their boron analogs have been optimized at the MP2͞6-31G** level by using the (8) package of programs. 13 C and 11 B NMR chemical shifts were calculated by the correlated GIAO-MP2 method (9, 10) (tzp͞dz basis set; refs. 9 and 10) using the ACES II programs (11). CH 5 ؉ and BH 5 . CH 5 ϩ (protonated methane) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
1
3
1
Order By: Relevance
“…The stability of the dihydrogen interaction with B is not unexpected given that the B center is electron-deficient such that formation of a σ-complex with a R−BH 2 (η 2 -H 2 ) moiety is energetically feasible without violating the classic octet rule . Indeed stable BH 3 (η 2 -H 2 ) molecules and BNH x dihydrogen intermediates are found in our calculations and also in previous research on boron systems. , …”
Section: Resultssupporting
confidence: 85%
“…The stability of the dihydrogen interaction with B is not unexpected given that the B center is electron-deficient such that formation of a σ-complex with a R−BH 2 (η 2 -H 2 ) moiety is energetically feasible without violating the classic octet rule . Indeed stable BH 3 (η 2 -H 2 ) molecules and BNH x dihydrogen intermediates are found in our calculations and also in previous research on boron systems. , …”
Section: Resultssupporting
confidence: 85%
“…In fact, the carbon resonance in methonium is quite shielded compared to methane. Our result (À18.1 ppm) differs from the value reported by Rasul et al, 24 (À11.5 ppm) which was calculated at the MP2 level of theory. Nevertheless, with both levels of theory, a significant shielding, of about 10 ppm, of the methonium 13 C resonance is predicted compared to methane, despite the coordination to a positively charged entity.…”
Section: Ch 4 and Ch 5 + As Modelscontrasting
confidence: 99%
“…Prakash et al reported an extension of the relationship to cage compounds containing trivalent carbon and boron atoms . Olah and Prakash et al also derived a similar empirical equation for the hypercoordinate carbocations (carbonium ions) and their corresponding hypercoordinate boron compounds. , A similar empirical equation for the hypercoordinate hydrido carbocations and their isoelectronic boron compounds was developed by us …”
Section: Introductionmentioning
confidence: 93%
“…5,6 A similar empirical equation for the hypercoordinate hydrido carbocations and their isoelectronic boron compounds was developed by us. 7 We now report our study of the relationship between GIAO-CCSD(T) calculated 11 B NMR chemical shifts of a series of interesting boronium and borenium ions and the 13 C NMR chemical shifts of the corresponding isoelectronic carbonium and carbenium ions, respectively. Calculations of the accurate 13 C NMR chemical shifts of organic molecules by DFT methods have recently been reviewed.…”
Section: ■ Introductionmentioning
confidence: 99%